Prototyping of Concurrent Control Systems with Application of Petri Nets and Comparability Graphs - Wisniewski, Remigiusz (2019)
This paper shows a novel prototyping technique for concurrent control systems described by interpreted Petri nets. The technique is based on the decomposition of an interpreted Petri net into concurrent sequential automata. In general, minimum decomposition requires runtime that is exponential in the number of Petri net places. We show that in many cases, including the real-life ones, the minimum decomposition problem can be solved in polynomial time. The proposed method allows implementing a concurrent control system using minimal number of sequential components, which requires polynomial time and can be applied to most of the considered cases. The presented concept is illustrated by a real-life industrial example of a beverage production and distribution machine implemented in a field programmable gate array.